Gene Expression and DNA Methylation Alterations During Non-alcoholic Steatohepatitis-Associated Liver Carcinogenesis - Dreval, Kostiantyn; Tryndyak, Volodymyr; de Conti, Aline; Beland, Frederick A.; Pogribny, Igor P. (Frontiers in Genetics, 2019)
Hepatocellular carcinoma (HCC) is one of the most aggressive human cancers. HCC is characterized by an acquisition of multiple abnormal phenotypes driven by genetic and epigenetic alterations, especially abnormal DNA methylation. The majority of existing clinical and experimental reports provide only a snapshot of abnormal DNA methylation patterns in HCC rather than their dynamic changes. This makes it difficult to elucidate the significance of these changes in the development of HCC. In the present study, we investigated hepatic gene expression and gene-specific DNA methylation alterations in mice using the Stelic Animal Model (STAM) of nonalcoholic steatohepatitis (NASH)-derived liver carcinogenesis. Analysis of DNA methylation in these genes showed the accumulation of DNA methylation abnormalities during the development of HCC, with the greatest number of aberrantly methylated genes being found in full-fledged HCC. Among these genes, only one gene, tubulin, beta 2B class IIB (Tubb2b), was increasingly hypomethylated and over-expressed at 6, 12, and 20 weeks. Furthermore, the TUBB2B gene was also over-expressed and hypomethylated in poorly differentiated human HepG2 cells as compared to well-differentiated HepaRG cells. The results of this study indicate that unique gene-expression alterations mediated by aberrant DNA methylation of selective genes may contribute to the development of HCC and may have diagnostic value as the disease-specific indicator.